DESIGNING OF DEVELOPED SURFACES OF COMPLEX PARTS - Tyshchenko, S. S.; Krasniuk, A. V.; Ulchenko, T. V.; Shcherbak, A. S. (Science and Transport Progress, 2017)
Purpose. The paper focuses on ensuring the rational choice of parameters of the mating surfaces of parts when designing process equipment based on the methods of artificial intelligence. Methodology. The paper considers the geometric model of a ruled developed surface, the conditions of existence of such a surface and provides a generalized algorithm for surface plotting regardless of the type of the working element or the machine-building product. One of the most common technical surfaces are the ruled ones, among which a special position is occupied by developed surfaces (thanks to their differential-parametric properties): surface tangent plane is n contact along the rectilinear generator and does not change its position in space when changing the point of contact; surfaces can be produced by bending sheet metal. These provisions enable a product manufacturer to save significant material and energy means, therefore, the development of geometric models of such surfaces is an important task. Findings. We analyzed the geometrical model of the developed surface which is incident to two guides. Experimental studies have shown the applicationprospectivity of semi-digger moldboards on moldboard plows, particularly on the double-deck ones. Taking into account the operating speed of the plow 2.8 m/s, the plant residues plowing percentage for plow with semi-digger moldboards is 98.9%, and with the digger ones – 96.1%. Originality. According to results: 1) the approaches to solving the problem of recognition of wear conditions of the tested interface, depicted by its conceptual model, were elaborated; 2) the corresponding algorithms of the computational procedures were built; 3) the mathematical model that determines the effect of the parameters of the contacting surfaces on their performance properties – linear wear rate during the normal wear and tear was developed; 4) for this model the theoretical prerequisite of use for the random mating study were designated. Practical value. Currently, these areas produced significant results which are in line with modern requirements of construction engineering. The process of parametric model optimization generates a plurality of desired values of the surface parameters. There are formed the algorithms for automatic recognition of design features and operation of interfaces by their images, which are set by a structured set of formal signs. The recognition result is the interface designation to a particular group, each of which corresponds to an individual computational model of quality parameters normalization.